Pengaruh Dukungan Spritual terhadap Tingkat Kecemasan pada Pasien Pre-Operasi - El Rahmayati; Ruth Novelina Silaban; Siti Fatonah (Jurnal Kesehatan, 2018)
Anxiety is an emotional response to the subjective judgment of individuals, influenced by the unconscious and not specifically known to cause. Based on data from the World Health Organization (WHO) in 2007, the United States analyzed data from 35,539 surgical clients treated in the intensive care unit from 2003 to 2006, of which 2,473 clients (7%) experienced anxiety conditions. The results of Masood Jawaid's research, et al.(2006) found that average respondents in a state of moderate anxiety as much as 57.65. The purpose of this study was to determine the effect of spiritual support on anxiety levels in pre-operative patients. This study was Quasi-Experiment with one group pretest-posttest design, sampling was using purposive sampling technique. Sample amounted to 16 respondents, population amounted to 325 patients. The Data collection tool was using a questionnaire sheet. The statistical test was using Wilcoxon test. The average yield of anxiety prior to therapy spiritual support was 49.88, with a standard deviation of 6.449. While the average anxiety after the therapy spiritual support was 46.81 with a standard deviation of 6.002. The statistical test result showed that p-value = 0.001, there was an effect of a spiritual support therapeutic to the level of anxiety of patients pre-operation at Imanuel Hospital Lampung Year 2017. This study suggested therapy for spiritual support as nursing care in patients who experience anxiety.